Прогнозування трафіку в локальних мережах, побудованих з використанням обладнання Juniper - Парінцев, Д. О. (ХНУРЕ, 2024)
Organizations of all sizes are looking for innovative solutions to improve the efficiency of their network infrastructure. One of the leading manufacturers in this field is Juniper Networks, known for its advanced technologies and wide range of products. Solving the network traffic prediction problem is of great interest in areas such as congestion control, loss control, and bandwidth allocation. The article examines the effectiveness of traffic forecasting algorithms in local networks taking into account fractality.
Keywords: прогнозування трафіку; обладнання Juniper